Captain Cook's Final Voyage : The Untold Story from the Journals of James Burney and Henry Roberts - Barnett, James K. (Book collections on Project MUSE., 2018)
Two young officers' extraordinary eyewitness accounts of Cook's search for the elusive Northwest Passage depict the captain's dramatic death, initial European contact, and Hawaii, Vancouver Island, and Alaska landings. The journals also offer early maps and the first Bering Sea ice pack reports. James K. Barnett adds context and expert commentary.